Asuhan Keperawatan pada An. A dengan Gangguan Sistem Muskuloskeletal: Post Operasi Ruptur Tendon Patella di Ruang Mawar 2 RSUD dr. Soeselo, Kabupaten Tegal - Marsela Dita Fahera; Ahmad Zakiudin; Sukirno Sukirno (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Disorders of the musculoskeletal system encompass a wide range of conditions affecting the bones, joints, and muscles. Bone-related disorders include osteoporosis, fractures, spinal deformities, osteopenia, osteomalacia, Paget’s disease of bone, osteopetrosis, achondroplasia, osteogenesis imperfecta, and osteomyelitis. Joint-related disorders consist of arthritis, bursitis, tendinitis, tendon injuries, tennis elbow, and carpal tunnel syndrome, while muscle disorders include myalgia, fibromyalgia, muscle injuries, muscular dystrophy, muscle atrophy, cramps, and spasms (Astuti et al., 2024). Fractures may lead to complications in surrounding tissues, such as soft tissue edema, bleeding into muscles and joints, joint dislocation, nerve damage, vascular injury, and tendon rupture (Rumapea, 2024). A patellar tendon rupture occurs when the fibrous tissue connecting the patella to the quadriceps muscle tears, and complete ruptures typically require surgical repair. The objective of this study was to design and implement a nursing care plan for patient A, who underwent post-operative management of a patellar tendon rupture in Mawar Ward 2 at RSUD dr. Soeselo, Tegal Regency, in 2025. This study applied a descriptive case study method. The findings revealed that the main complaint reported by the patient was pain in the left knee. Three nursing diagnoses were identified: acute pain, impaired physical mobility, and risk of infection. Nursing interventions were structured based on standardized guidelines from SDKI, SLKI, and SIKI, enabling systematic implementation. The results highlight the importance of comprehensive and evidence-based nursing care to optimize recovery outcomes for patients with post-operative tendon rupture.